Manual penjagaan khas untuk orang kurang upaya - Hasan, Haliza; Abdul Hamid, Siti Hazariah; Mohd, Farah Natashah; Jaafar, Nurul Hazirah; Asmadi, Nur Izzati; Megat Mohd Azlan, Megat Ridzuan; Mustapa, Nurayunisha; Isa, Nor Farihatasha; Idrus, Nurul Hanis; Ag. Damit, Aifa Syazwani; Che Sulaiman, Fathin Nursyafiqah Juara; Nik Rusli, Nik Nor Amani (2021)
The Special Care Manual (SCM) Version 2.0 is an improvement from version 1.0. This SCM was designed as a manual guide for caring for people with special needs mainly to be used by the Community-Based Rehabilitation Centre, in Kuantan and will be expanded the implementation to other CBRs for the whole Pahang. This disclosure consisted of 4 parts; Personal Hygiene, Sexual Health, Oral Care, and Diet Intake for people with special needs. This version 2.0 was designed after a comprehensive review by the Special Care Team members based on the needs of this group of people (Disabled). The digital manual guide was developed suitable for daily use and friendly user for the caregivers of people with special needs.